Sistem Informasi Layanan Klaim Asuransi Berbasis Web Pada Ajb Bumiputera 1912 Kantor Cabang Telanaipura Jambi - Tyas Rahayu, Ati; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2023)
AJB Bumiputera 1912 Telanaipura Jambi Branch Office is an insurance company that provides services to the community. In the current system, the claim submission service process is still done manually, that is, submitting claims can only be processed if the agent and customer have a meeting and the customer completes a claim submission form. This causes the length of the claim submission process and the services provided do not run optimally. Based on the existing problems, a claim submission service system is needed in order to assist AJB Bumiputera 1912 Telanaipura Jambi Branch Office in terms of claim submission services. The purpose of this research is to design a prototype of the claim submission service system using the system modeling tool, namely UML and the diagrams used include use case diagrams, activity diagrams, and class diagrams. The results of this research are in the form of designing a prototype claim submission service system that can be implemented by AJB Bumiputera 1912 Telanaipura Jambi Branch Office to help facilitate the management of information on life insurance claims submissions.